Relation of sensory peripheral neuropathy in sjögren syndrome to Anti-Ro/SSA (2012)
Background: Sjögren syndrome is a common, chronic autoimmune disease that typically produces inflammation and poor function of the salivary and lacrimal glands. Other organs can be affected, including the nervous system. Sensory peripheral neuropathy is a common manifestation of the disease. Methods: Eight-eight patients attending a dry eyesYdry mouth clinic were diagnosed to have primary Sjögren syndrome and underwent a neurological examination. Anti-Ro (or SSA) and anti-La (or SSB) were determined using immunodiffusion as well as Inno-Lia and BioPlex ANA screen. Serum vitamin B12 levels were determined using an enzyme-linked microtiter plate assay. Results: Twenty-seven (31%) of the 88 patients had peripheral neuropathy as defined by loss of light touch, proprioception, or vibratory sensation. Anti-Ro and anti-La were found by immunodiffusion in 12 patients, and 8 of these 12 had neuropathy (W2 = 8.46, P = 0.0036, odds ratio = 6.0 compared to those without precipitating anti-Ro and anti- La). Of the 27 patients with only anti-Ro by immunodiffusion, 13 (48.1%) had neuropathy (W2 = 5.587, P = 0.018, compared to those without anti-Ro). There was no relationship of the other, more sensitive measures of anti-Ro and anti-La to neuropathy. In addition, we found no association of serum vitamin B12 levels to neuropathy among these patients with Sjögren syndrome. Conclusions: Sensory peripheral neuropathy is common among patients with Sjögren syndrome and is associated with the presence of anti-Ro and anti-La when determined by immunodiffusion. Copyright © 2012 by Lippincott Williams and amp; Wilkins.